Histopathology of mitochondrial cytopathy and the Laurence-Moon-Biedl syndrome. Issue 10 (October 1986) - Runge, P; Calver, D; Marshall, J; Taylor, D
Abstract : Clinical and histopathological studies of two patients with distinctly different inherited juvenile retinal dystrophies indicate that the ocular defect in mitochondrial cytopathy involves the underlying pigment epithelium, whereas in the Laurence-Moon-Biedl syndrome the photoreceptor cells are primarily affected.